Two cases of deep vein thrombosis associated with a combined paroxetine and zotepine therapy - Pantel, Johannes; Schröder, Johannes; Eysenbach, Katrin; Mundt, Christoph (Pharmacopsychiatry, 1997)
Thieme E-Books & E-Journals
Gesehen am 22.01.2021